2017
DOI: 10.5964/jnc.v3i1.71
|View full text |Cite
|
Sign up to set email alerts
|

Creating a context for learning: Activating children’s whole number knowledge prepares them to understand fraction division

Abstract: When children learn about fractions, their prior knowledge of whole numbers often interferes, resulting in a whole number bias. However, many fraction concepts are generalizations of analogous whole number concepts; for example, fraction division and whole number division share a similar conceptual structure. Drawing on past studies of analogical transfer, we hypothesize that children’s whole number division knowledge will support their understanding of fraction division when their relevant prior knowledge is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 51 publications
2
17
0
1
Order By: Relevance
“…Importantly, because warm-up activities tend to reactivate very familiar prior knowledge, the specific characteristics of examples used in the initial learning context of that prior knowledge should be much less important than the characteristics of the warm-up activity that serves to reactivate prior knowledge. Finally, in line with Day and Goldstone’s (2012) conceptualization of transfer, we also suggest that warm-up activities may be especially powerful when they involve spatial representations (e.g., Thompson & Opfer, 2010) and physical or imagined action (e.g., Sidney & Alibali, 2017). Future work is needed to test these hypotheses for implementing implicit analogical instruction and the circumstances under which implicit analogy might (or might not) be effectively activated within and outside of the domain of math.…”
Section: Leveraging Children’s Prior Knowledgesupporting
confidence: 72%
See 1 more Smart Citation
“…Importantly, because warm-up activities tend to reactivate very familiar prior knowledge, the specific characteristics of examples used in the initial learning context of that prior knowledge should be much less important than the characteristics of the warm-up activity that serves to reactivate prior knowledge. Finally, in line with Day and Goldstone’s (2012) conceptualization of transfer, we also suggest that warm-up activities may be especially powerful when they involve spatial representations (e.g., Thompson & Opfer, 2010) and physical or imagined action (e.g., Sidney & Alibali, 2017). Future work is needed to test these hypotheses for implementing implicit analogical instruction and the circumstances under which implicit analogy might (or might not) be effectively activated within and outside of the domain of math.…”
Section: Leveraging Children’s Prior Knowledgesupporting
confidence: 72%
“…In our own work (Sidney & Alibali, 2015, 2017; Sidney, Thompson, & Rivera, 2019; Thompson & Opfer, 2010), we have demonstrated that children engage in more accurate problem solving and efficient learning in challenging domains when their highly practiced, relevant prior knowledge has been recently activated using warm-up activities designed to instantiate an implicit analogy. For example, we demonstrated that children’s conceptual understanding of fraction division was more likely to be accurate when structurally similar whole-number division concepts were recently practiced (Sidney & Alibali, 2017). When children had just modeled whole-number division problems using physical objects to show division by partitioning a given amount into groups, they were more likely to accurately model fraction division compared with children who modeled related but structurally dissimilar fraction multiplication immediately before fraction division.…”
Section: Leveraging Children’s Prior Knowledgementioning
confidence: 94%
“…For example, comparison, contrast, relational language, and structural alignment are known to improve relational learning (Christie & Gentner, 2010, 2014Gentner, 2010;Kurtz, Boukrina, & Gentner, 2013), and instructional methods that use these techniques may prove beneficial if adapted for use with fractions. However, there is much work yet to be done to determine how best to translate the findings from the lab to the classroom; for example, although introducing fraction division by analogy to whole number division has shown some benefits, some adjustments may need to be made to this approach before it is more widely effective (Sidney & Alibali, 2015;Sidney & Alibali, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Participants were given three minutes to solve each set of six problems. Two problems in each section involved two fraction operands (Siegler et al, 2011), and four problems involved a whole number and a fraction (Sidney & Alibali, 2017). The variable was calculated as the number of correctly answered questions.…”
Section: Arithmetic Accuracymentioning
confidence: 99%